Genome-Wide Analysis of Sorghum GT47 Family Reveals Functional Divergences of MUR3-Like Genes - Xu, Hua; Ding, Anming; Chen, Sihui; Marowa, Prince; Wang, Dian; Chen, Min; Hu, Ruibo; Kong, Yingzhen; O’Neill, Malcolm; Chai, Guohua; Zhou, Gongke (Frontiers in Plant Science, 2018)
Sorghum (Sorghum bicolor) is an important bioenergy crop. Its biomass mainly con-sists of the cellulosic and non-cellulosic polysaccharides, both which can be converted to biofuels. The biosynthesis of non-cellulosic polysaccharides involves several gly-cosyltransferases (GT) families including GT47. However, there was no systemic study on GT47 family in sorghum to date. Here, we identified 39 sorghum GT47 fam-ily members and showed the functional divergences of MURUS3 (MUR3) homologs. Sorghum GT47 proteins were phylogenetically clustered into four distinct subfamilies. Within each subfamily, gene structure was relatively conserved between the members. Ten gene pairs were identified from the 39 GT47 genes, of which two pairs might be originated from tandem duplication. 25.6% (10/39) of sorghum GT47 genes were homologous to Arabidopsis MUR3, a xyloglucan biosynthesis gene in primary cell walls. SbGT47_2, SbGT47_7 and SbGT47_8, three most homologous genes of MUR3, exhibited different tissue expression patterns and were selected for complementation into Arabidopsis mur3-3. Physiological and cell wall analyses showed that SbGT47_2 and SbGT47_7 may be two functional xyloglucan galactosyltransferases in sorghum. Further studies found that MUR3-like genes are widely present in the seed plants but not in the chlorophytic alga Chlamydomonas reinhardtii. Our results provide novel information for evolutionary analysis and functional dissection of sorghum GT47 family members.